Researching volunteers: going beyond - Smith, K.; Holmes, Kirsten (Australian and New Zealand Association for Leisure Studies (ANZALS), 2009)
Volunteers make contributions across the breadth of tourism, both as volunteer tourists and as volunteer tourists and as volunteers supporting tourism within their local community, such as through visitor attractions and events. While tourism volunteering as a research field is growing, these two groups of volunteers have largely been considered separately with little crossover of research or researchers. This paper proposes a model of tourism volunteer engagements as a means of conceptualising types of tourism volunteering, settings and time contributions more holistically and inclusively. Using this model as a framework, we set out the current state of research on tourism volunteering, demonstrating that, to date, researchers have concentrated on key types of tourism volunteering and settings, and within these, focused on dominant time contributions, roles and perspectives, and prevailing methods and approaches. By identifying gaps in extant research we call for more critical research and challenge researchers to 'go beyond' and create a wider-ranging and more inclusive research agenda. By taking up the challenge to 'go beyond' we argue that this nascent research field can matutre and indeed develop a wider-ranging and more inclusive research agenda that embraces both the diversity and commonalities of tourism volunteering.